Assessment of the challenge of sustainable recycling of municipal solid waste management in India. (2nd August 2010) - Khajuria, Anupam; Matsui, Takanori; Machimura, Takashi; Morioka, Tohru
Municipal solid waste management is one of the most serious and most neglected areas of urban development which create environmental hazards confronting municipalities. Qualitative analysis of municipal solid waste in India identified barriers or incentives for recycling, resulted in the development factors. The PSIR framework with sensitive analysis is approach towards the focus on sustainable development. Necessary and beneficial relationship drawn among development factors revealed the collaborative web model for sustainable municipal solid waste management. The functionality of other factors in collaborative relationship greatly influences the success of sustainable municipal solid waste management in developing countries as India.